2014
DOI: 10.1111/jwas.12108
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soybean Lecithin Supplementation to a Practical Diet Formulation on Juvenile Channel Catfish, Ictalurus punctatus: Growth, Survival, Hematology, Innate Immune Activity, and Lipid Biochemistry

Abstract: A feeding trial was conducted to determine the effects of soy lecithin supplementation on production performance of juvenile channel catfish, Ictalurus punctatus (mean ± SE; 5.8 ± 0 g). The basal diet consisted of a practical dietary formulation for channel catfish, containing 4.3% endogenous phospholipids (PL) from dietary ingredients, to which supplemental PL from soybean lecithin were added. The study diets were 1 control and 2 experimental diets to which 0, 2, or 4% supplemental lecithin was added, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Tissue protein in the present study was also increased with increasing Lysomax concentration. Similar results were also reported in channel catfish fed graded levels of dietary lecithin (Sink & Lochmann, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Tissue protein in the present study was also increased with increasing Lysomax concentration. Similar results were also reported in channel catfish fed graded levels of dietary lecithin (Sink & Lochmann, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, larger fish may not benefit from supplemental PL, due to their capacity to synthesize PL from dietary precursors (Poston, 1990). On the other hand, supplemental soy lecithin did not affect survival, growth rates and feed efficiency in fingerling and juvenile channel catfish (Sink & Lochmann, 2014; Stickney & Andrews, 1972).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sun, Wu, Zhang, Yue, and Qi (2010) showed that the contents of total phospholipid and PC in eggs were significantly increased relative to the control group when 0.5%, 1.0%, 2.0% and 4.0% SL was added in laying hens. Sink and Lochmann (2014) reported that PC content was greater in catfish fed 2% or 4% lecithin than fed 0% lecithin. Additionally, SL is one of the sources of choline and fatty acids.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies were a collaboration with economist/Center Director Dr. C. R. “Carole” Engle, who was running feeding trials with catfish to establish the most profitable production practices, and with the NWAC in Mississippi. Several trials were conducted involving the grow‐out of catfish, including investigating alternative feedstuffs (Engle, Kumar, Lochmann, Bosworth, & Thompson, ; R. Lochmann et al, ; R. T. Lochmann, Islam, Phillips, Adam, & Everette, ; Pugliese, Heikes, Engle, Bosworth, & Lochmann, ; Renukdas et al, ; Sink & Lochmann, ), prebiotics (Thompson, Lochmann, Phillips, & Sink, ), lipid sources (Faukner et al, , ; Sink & Lochmann, ; Suja, Lochmann, Sink, Phillips, & Chen, ), dietary protein and feeding frequency (Engle, Ruebush, Leyva, & Trimpey, ), and winter feeding (Bastola, Engle, Haukenes, & Freeman, ; Nanninga, Engle, Stone, & Goodwin, ). Research was also conducted on the nutrition of catfish fry (Sink, Lochmann, & Kinsey, ) and broodfish (Sink & Lochmann, ; Sink, Lochmann, Pohlenz, Buentello, & Gatlin, ).…”
Section: To Presentmentioning
confidence: 99%